Animation Video Media Using Directed Reading Thinking Activity (DRTA) Strategies Improve Reading Understanding of Indonesian Language - Ni Nyoman Ganing; I Gusti Agung Ayu Wulandari (International Journal of Elementary Education, 2023)
The difficulties students face, especially in reading comprehension activities, are that they need help understanding the contents of the stories they have read, so they are less able to answer questions related to the contents of the reading. The difficulties faced by these students were because students needed to be included in communicating and contributing to learning activities. This study aims to analyze animated video media with the directed reading thinking activity (DRTA) strategy for reading comprehension in Indonesian. This research is a quasi-experimental, posttest-only design with no treatment control design. The population is all 9 classes of fourth-grade elementary school, with 327 students. Determination of the research sample using a random sampling technique. Non-test method data collection. The data collection instrument is Observation. The data analysis method is the inferential statistical analysis method. The method of data analysis is an inferential statistical analysis technique and t-test. The study results showed a significant influence on the ability to read Indonesian language comprehension between the group taught the Directed Reading Thinking Activity (DRTA) strategy and the group taught using conventional learning in fourth-grade elementary school students. It was concluded that animated video media with the directed reading thinking activity (DRTA) strategy could improve reading comprehension skills in Indonesian.